Klausula Akad Rahn Dari Perspektif Hukum Islam Dan Urgensi Notaris Dalam Penyusunannya - Ihyannisak Zain; Syahrizal Abbas; Zahratul Idami (Jurnal Hukum IUS QUIA IUSTUM, 2019)
The practice of Shari‘a Court, especially rahn contracts in the form of standard clauses, still have a number of problems, including the norms of the contents of the contract. This study discusses first, whether the norms in the contents of the rahn contract on Sharia Pawnshop (pegadian Syariah) are in accordance with the provisions of Islamic law. Second, the urgency of notary involvement in the formulation of the Sharia pawnshop rahn contract clause in an effort to guarantee consumer protection. The methodology used in this research is a normative study with secondary data sources derived from legal materials, with a statutory and conceptual approach. This research concludes: first, the norm contained in the contents of the rahn contract on Sharia Pawnshop is not in accordance with the provisions of Islamic law because it contains the invalid (fasid) conditions of a contract. Second, the need for the involvement of a Notary Public to safeguard any predetermined rules regarding rahn contracts to be carried out, as well as efforts to ensure legal protection for consumers to secure the position between rahin and murtahin for it to become balanced for the rahn contract clause to be based on justice.